Chapter 3.7 Evolution of Professional Identity in Research Management and Administration - Mariko Yang-Yoshihara; Susi Poli; Simon Kerridge (Emerald Publishing Limited, 2023)
This chapter delves into the evolving identity of professionals within the field of research management and administration (RMA), examining the shifts in their roles and expectations in the changing landscape in higher education. After the introductory section, Section 2 offers a conceptual framework that emphasises identity as a dynamic process rather than a static concept. This framework sheds light on the changing roles and expectations that define the RMA profession. In Section 3, we explore the contextual backdrop of shifting expectations surrounding RMA roles while stressing the importance of recognizing the multiplicity of identities to comprehend the nuances of the RMA profession. Section 4 analyzes empirical data and explore the diverse pathways that lead individuals into the RMA profession. We uncover that a notable proportion of RMAs possess scientific training and research experience and highlight the complexities surrounding the identity of RMAs with doctoral training (DRMAs). Lastly, Section 5 discusses key observations that yield valuable insights for future research on the evolving professional identity of RMAs. We emphasise that, through self-exploration and introspection, practitioners in the field can contribute to a deeper understanding of their roles and actively shape their professional identity.
10.1108/978-1-80382-701-820231025; 10.1108/978-1-80382-701-820231025; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262